Two Hormones for One Receptor: Evolution, Biochemistry, Actions, and Pathophysiology of LH and hCG - Casarini, Livio; Santi, Daniele; Brigante, Giulia; Simoni, Manuela (Endocrine reviews, 2018)
Abstract LH and chorionic gonadotropin (CG) are glycoproteins fundamental to sexual development and reproduction. Because they act on the same receptor (LHCGR), the general consensus has been that LH and human CG (hCG) are equivalent. However, separate evolution of LHβ and hCGβ subunits occurred in primates, resulting in two molecules sharing ~85% identity and regulating different physiological events. Pituitary, pulsatile LH production results in an ~90-minute half-life molecule targeting the gonads to regulate gametogenesis and androgen synthesis. Trophoblast hCG, the "pregnancy hormone," exists in several isoforms and glycosylation variants with long half-lives (hours) and angiogenic potential and acts on luteinized ovarian cells as progestational. The different molecular features of LH and hCG lead to hormone-specific LHCGR binding and intracellular signaling cascades. In ovarian cells, LH action is preferentially exerted through kinases, phosphorylated extracellular-regulated kinase 1/2 (pERK1/2) and phosphorylated AKT (also known as protein kinase B), resulting in irreplaceable proliferative/antiapoptotic signals and partial agonism on progesterone production in vitro. In contrast, hCG displays notable cAMP/protein kinase A (PKA)-mediated steroidogenic and proapoptotic potential, which is masked by estrogen action in vivo. In vitro data have been confirmed by a large data set from assisted reproduction, because the steroidogenic potential of hCG positively affects the number of retrieved oocytes, and LH affects the pregnancy rate (per oocyte number). Leydig cell in vitro exposure to hCG results in qualitatively similar cAMP/PKA and pERK1/2 activation compared with LH and testosterone. The supposed equivalence of LH and hCG has been disproved by such data, highlighting their sex-specific functions and thus deeming it an oversight caused by incomplete understanding of clinical data.